Modeling female employees’ ability to telecommute in Kuala Lumpur - M.Jaff, Mootaz; Kadar Hamsa, Abdul Azeez (Finnish Transport and Communication Agency Traficom, 2020)
Telecommuting is considered to be most apt for female workforce due to their added responsibilities to balance both work and family matters. This paper models the ability of female employees to telecommute in the selected business organizations in Kuala Lumpur, Malaysia. Four job categories namely “clerical workers”, “professionals”, “associate professionals”, and “managers” were selected to ascertain their perceptions on telecommuting through a questionnaire survey. A binary and an ordinal logistic regression model were used to evaluate the effects of the explanatory variables on the ability to telecommute. The results of the model reveal that ‘prior experience working from home and ‘increased frequency of telephone usage’ almost doubles the ability to telecommute, whereas ‘time spent working with others’ and the ‘usage of the photocopier’ reduces it. Managers, Associate Professionals, Professionals were 3.5, 2.3 and 1.5 times more likely to be able to telecommute more frequently than Clerical workers.